2020
DOI: 10.37932/j.e.v10i2.117
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Literasi Keuangan Pedagang Di Pasar Oesapa Kota Kupang Nusa Tenggara Timur

Abstract: This research aims to analyze the literacy levels of Oesapa Market traders. This research is a quantitative descriptive by using survey method. There are four indicators that used in this research, that indicators are: 1) Financial Knowledge,2) Financial Behaviour, 3) Financial attitudes and 4) Banking Technology. The population in this study was all traders in Oesapa Market and the sample in the study were 90 respondents from the entire population. Primary data were obtained from respondents by using question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Sine et al, [7] study result found that overall, based on the indicators of financial literacy, it can be said that the financial literacy of traditional market seller in Oesapa Market was categorised medium. It means that they have knowledge and trust to formal financial institution but they did not have skills in utilising the products and services of the financial institution.…”
Section: Empirical Studymentioning
confidence: 94%
“…Sine et al, [7] study result found that overall, based on the indicators of financial literacy, it can be said that the financial literacy of traditional market seller in Oesapa Market was categorised medium. It means that they have knowledge and trust to formal financial institution but they did not have skills in utilising the products and services of the financial institution.…”
Section: Empirical Studymentioning
confidence: 94%
“…Literasi keuangan atau kesadaran atas pengelolaan keuangan melihatkan bahwa seseorang tersebut memiliki modal untuk ketercapaian kesejahteraan keuangan [3]. Literasi keuangan mengacu pada proses atau kegiatan mendidik masyarakat tentang keuangannya dan komponennya untuk lebih memahami keuangan dan komponennya dan membantu mereka dalam mencapai tujuan keuangan yang diinginkan [4]. Literasi keuangan dapat membantu seseorang jauh dari resiko keuangan dan kesalahan dalam pengelolaan keuangan, sebab malasah keuangan tidak seluruhnya disebabkan oleh besaran pendapatan yang diperoleh seseorang [5].…”
Section: Pendahuluanunclassified
“…(Widayati, 2012). Menurut Suryani (2008), factor-faktor yang mempengaruhi pembentukan sikap adalah pengalaman langsung, keluarga, teman sebaya, pemasaran langsung dan tayangan media masa.…”
Section: Telaah Pustakaunclassified